If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3y + -20)(y + 10) * 70 = 180 Reorder the terms: (-20 + 3y)(y + 10) * 70 = 180 Reorder the terms: (-20 + 3y)(10 + y) * 70 = 180 Reorder the terms for easier multiplication: 70(-20 + 3y)(10 + y) = 180 Multiply (-20 + 3y) * (10 + y) 70(-20(10 + y) + 3y * (10 + y)) = 180 70((10 * -20 + y * -20) + 3y * (10 + y)) = 180 70((-200 + -20y) + 3y * (10 + y)) = 180 70(-200 + -20y + (10 * 3y + y * 3y)) = 180 70(-200 + -20y + (30y + 3y2)) = 180 Combine like terms: -20y + 30y = 10y 70(-200 + 10y + 3y2) = 180 (-200 * 70 + 10y * 70 + 3y2 * 70) = 180 (-14000 + 700y + 210y2) = 180 Solving -14000 + 700y + 210y2 = 180 Solving for variable 'y'. Reorder the terms: -14000 + -180 + 700y + 210y2 = 180 + -180 Combine like terms: -14000 + -180 = -14180 -14180 + 700y + 210y2 = 180 + -180 Combine like terms: 180 + -180 = 0 -14180 + 700y + 210y2 = 0 Factor out the Greatest Common Factor (GCF), '10'. 10(-1418 + 70y + 21y2) = 0 Ignore the factor 10.Subproblem 1
Set the factor '(-1418 + 70y + 21y2)' equal to zero and attempt to solve: Simplifying -1418 + 70y + 21y2 = 0 Solving -1418 + 70y + 21y2 = 0 Begin completing the square. Divide all terms by 21 the coefficient of the squared term: Divide each side by '21'. -67.52380952 + 3.333333333y + y2 = 0 Move the constant term to the right: Add '67.52380952' to each side of the equation. -67.52380952 + 3.333333333y + 67.52380952 + y2 = 0 + 67.52380952 Reorder the terms: -67.52380952 + 67.52380952 + 3.333333333y + y2 = 0 + 67.52380952 Combine like terms: -67.52380952 + 67.52380952 = 0.00000000 0.00000000 + 3.333333333y + y2 = 0 + 67.52380952 3.333333333y + y2 = 0 + 67.52380952 Combine like terms: 0 + 67.52380952 = 67.52380952 3.333333333y + y2 = 67.52380952 The y term is 3.333333333y. Take half its coefficient (1.666666667). Square it (2.777777779) and add it to both sides. Add '2.777777779' to each side of the equation. 3.333333333y + 2.777777779 + y2 = 67.52380952 + 2.777777779 Reorder the terms: 2.777777779 + 3.333333333y + y2 = 67.52380952 + 2.777777779 Combine like terms: 67.52380952 + 2.777777779 = 70.301587299 2.777777779 + 3.333333333y + y2 = 70.301587299 Factor a perfect square on the left side: (y + 1.666666667)(y + 1.666666667) = 70.301587299 Calculate the square root of the right side: 8.384604183 Break this problem into two subproblems by setting (y + 1.666666667) equal to 8.384604183 and -8.384604183.Subproblem 1
y + 1.666666667 = 8.384604183 Simplifying y + 1.666666667 = 8.384604183 Reorder the terms: 1.666666667 + y = 8.384604183 Solving 1.666666667 + y = 8.384604183 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1.666666667' to each side of the equation. 1.666666667 + -1.666666667 + y = 8.384604183 + -1.666666667 Combine like terms: 1.666666667 + -1.666666667 = 0.000000000 0.000000000 + y = 8.384604183 + -1.666666667 y = 8.384604183 + -1.666666667 Combine like terms: 8.384604183 + -1.666666667 = 6.717937516 y = 6.717937516 Simplifying y = 6.717937516Subproblem 2
y + 1.666666667 = -8.384604183 Simplifying y + 1.666666667 = -8.384604183 Reorder the terms: 1.666666667 + y = -8.384604183 Solving 1.666666667 + y = -8.384604183 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1.666666667' to each side of the equation. 1.666666667 + -1.666666667 + y = -8.384604183 + -1.666666667 Combine like terms: 1.666666667 + -1.666666667 = 0.000000000 0.000000000 + y = -8.384604183 + -1.666666667 y = -8.384604183 + -1.666666667 Combine like terms: -8.384604183 + -1.666666667 = -10.05127085 y = -10.05127085 Simplifying y = -10.05127085Solution
The solution to the problem is based on the solutions from the subproblems. y = {6.717937516, -10.05127085}Solution
y = {6.717937516, -10.05127085}
| 10/87=x/100 | | s(n)=(1/4)n | | -7+2y=2y | | 8+2x-7-5x=3x+2-9x | | sin22=X/17 | | p*1=2 | | .4(d-2)=.3d+9-1+.1d | | -2x-4x=-3(-4x-6)+6(7-8x) | | v*8=16 | | -15k+9k=36 | | 4x+5/2x=1/2 | | 2z+16=58 | | 3d-4=d+11 | | 2(1.5y+2)=3y+4 | | 16=2x-4x | | -7c+10c=33 | | p+p+81=180 | | 3(t-4)-2(2t+3)=-4 | | 18=-9v | | 21-22= | | 3(x+12)=3x+12 | | 2p+81= | | Y+1.91=8.75 | | 4+6(n)=9(n)+10 | | -6=x-2-8 | | b+3.5=5.21 | | 6.25t=44.25 | | 4(-8x+-5)=-32x-26 | | 5x-6=3x+22 | | 8-7(n)=4+3(n) | | (4/25)^2×2^4(15/2) | | (3x+16)=(11x-18) |